PENGARUH PERSENTASE ABU SEKAM PADI DAN GULA TEBU GULA TERHADAP KARAKTERISASI MORTAR KURVA KEKUATAN DENGAN KOMPRESI PEMUATAN AKSIAL - Cut Yusnar (Politeknik Negeri Lhokseumawe, 2013)
An experiment was conducted to investigate the characterization of strength Curve as the influence of adding Rice Husk Ash and Sugar Cane Bagasse Ash under Compressive of axial Loading. Six series of test specimens which was consist of two series of normal mortal specimens, two series of rice husk ash mortal specimens with 10 % and 20 % of cement replacement. Two series of Sugar Cane Bagasse Ash mortal specimens which was consist of 10 % and 20 % of cement replacement. Test result indicated that the mortar strength curve of Sugar Cane Bagasse has higher than strength curve of Rice Husk Ash Specimens and normal Strength concrete.